Firm Exit and Exchange Rates: An Examination with Turkish Firm-Level Data - Nazlı Karamollaoğlu; M. Ege Yazgan (Koç University-TÜSİAD Economic Research Forum (ERF), 2014)
Micro-level empirical research has begun to obtain important results on the effects of currency variations on firms' survival. To date, the literature has lacked detailed analysis of the effects of exchange rates on firms' survival behavior in emerging markets due to a scarcity of firm level information. Using a unique firm-level dataset, we test the impact of currency appreciation on the survival behavior of Turkish firms in manufacturing industries for 2002-2009. The results suggest that real exchange rate appreciation decreases the probability of survival in manufacturing industries. We also find that high (low) productivity firms have higher (lower) probability of survival than low (high) productivity firms as a result of domestic exchange rate appreciation. This evidence indicates that economic events/policies leading to appreciation in domestic currency should be cautiously managed, especially in a resource constrained emerging market economy such as Turkey.
Keywords: F14; F31; F41; 330; Exchange rate; firm-level; export; emerging markets; survival